Cigarette smoke-induced alveolar epithelial–mesenchymal transition is mediated by Rac1 activation - Shen, Hui-juan; Sun, Yan-hong; Zhang, Shui-juan; Jiang, Jun-xia; Dong, Xin-wei; Jia, Yong-liang; Shen, Jian; Guan, Yan; Zhang, Lin-hui; Li, Fen-fen; Lin, Xi-xi; Wu, Xi-mei; et al. (Biochimica et biophysica acta, 2014)
Epithelial-mesenchymal transition (EMT) is the major pathophysiological process in lung fibrosis observed in chronic obstructive pulmonary disease (COPD) and lung cancer. Smoking is a risk factor for developing EMT, yet the mechanism remains largely unknown. In this study, we investigated the role of Rac1 in cigarette smoke (CS) induced EMT. EMT was induced in mice and pulmonary epithelial cells by exposure of CS and cigarette smoke extract (CSE) respectively. Treatment of pulmonary epithelial cells with CSE elevated Rac1 expression associated with increased TGF-β1 release. Blocking TGF-β pathway restrained CSE-induced changes in EMT-related markers. Pharmacological inhibition or knockdown of Rac1 decreased the CSE exposure induced TGF-β1 release and ameliorated CSE-induced EMT. In CS-exposed mice, pharmacological inhibition of Rac1 reduced TGF-β1 release and prevented aberrations in expression of EMT markers, suggesting that Rac1 is a critical signaling molecule for induction of CS-stimulated EMT. Furthermore, Rac1 inhibition or knockdown abrogated CSE-induced Smad2 and Akt (PKB, protein kinase B) activation in pulmonary epithelial cells. Inhibition of Smad2, PI3K (phosphatidylinositol 3-kinase) or Akt suppressed CSE-induced changes in epithelial and mesenchymal marker expression. Altogether, these data suggest that CS initiates EMT through Rac1/Smad2 and Rac1/PI3K/Akt signaling pathway. Our data provide new insights into the fundamental basis of EMT and suggest a possible new course of therapy for COPD and lung cancer.